Short-Term and Chronic Effects of Aerobic and Resistance Exercise on Sleep in Young Men - Drenowatz Clemens; D. Wirth Michael; L. Grieve George (Journal of Preventive Medicine And Care, 2017)
Despite the generally accepted benefits of exercise on sleep there remains limited research on potential differential effects by exercise type. The purpose of the present study was to examine short-term and chronic effects of aerobic and resistance exercise on various sleep quality parameters, as well as sleep duration. Generally healthy, previously sedentary young (27±3 years) men completed a 16-week aerobic and 16-week resistance exercise program in random order separated by a minimum of 6 weeks with no formal exercise. Each exercise program consisted of three supervised exercise sessions per week. Quality and duration of sleep was determined with a multi-sensor device that was worn prior to, during week 1 and week 16 of each exercise program. A total of 8 participants provided valid data on time spent awake after sleep onset, sleep latency, total sleep time, sleep efficiency and time spent in bed for both exercise programs. During week 1, aerobic exercise was associated with a significant decline in sleep latency (-6.5±6.8 min) and time in bed (-39.2±42.2 min) while resistance exercise was associated with a decline in time spent awake after sleep onset (-21.6±16.7 min) and increased sleep efficiency (4.3±4.8 %). Effects were no longer significant after 16 weeks of exercise. These results indicate that aerobic and resistance exercise have beneficial effects on quality of sleep, particularly in the short-term, but the specific exercise-induced changes vary by exercise type.
Keywords: physical activity